Meningkatkan Kemampuan Bahasa Anak melalui Metode Bercerita pada Anak Usia 5-6 Tahun - Athena Sahadatunnisa; Astuti Darmiyanti; Nida’ul Munafiah (AS-SABIQUN, 2023)
Providing stimulation through early childhood education needs to be given comprehensively, in the sense that children are not only intelligent in their brains, but also intelligent in other aspects of their lives. One of the intelligences that is important and needs to be stimulated is language development. The type of research used by researchers.Classroom action research is a form of research carried out by teachers in carrying out their main tasks, namely managing the implementation of teaching and learning activities (KBM). B is still not optimal. The methods and media used must vary, for example the teacher uses additional media such as audio-visual media, so when the child is unable to express his language through stories, the teacher invites the child to watch and listen to a story from a children's film, then after finishing the teacher instructs the child to pour it back through the story according to their own imagination. so that as it can be concluded that children are not easily bored and will continue to be enthusiastic and children's language skills will be trained and continue to improve.